Pokémon : The Orange League [anglicky] / Book 3 - West, Tracey, 1965- (Orchard Books, 2021)
Since arriving on the Orange Islands, Ash has won every single one of his battles! But is he up to the Four-Star Challenge? Ash must tackle totally new ground - and learn some valuable lessons about himself - before he can win all four star gems, and earn himself a place on the legendary Orange League.